Applying network analysis to assess coastal risk planning. (1st August 2018) - Roca, Elisabet; Julià-Verdaguer, Anna; Villares, Míriam; Rosas-Casals, Martí
Abstract: Adequate response to risks affecting coasts requires an integrated and coordinated multi-risk governance system, with ongoing evaluation of statutory planning documents and responsible stakeholders. Traditionally, such analyses have been carried out using mainly qualitative approaches. This paper adopts a more systemic and quantitative perspective on assessing planning systems and stakeholder relationships in connection with coastal risk. We apply network analysis to the Catalan coast (Northwestern Mediterranean Basin), paying special attention to the level of climate change integration in the planning system, as an aggravating factor of current risk dynamics. Our results demonstrate and quantify the complexity of Catalan coastal risk planning, which requires dealings with multi-level legal and administrative frameworks. Also highlighted is dissimilar management traditions according to risk type: the perspective on flooding risk is more unified and multi-risk focused, whereas coastal erosion (a significant issue for the Catalan coast) is managed more sectorially from a centralized administrative level. Climate change, moreover, is weakly accounted for in current statutory planning. We also acknowledge the relevance of using qualitative information as an important complement in interpreting results and making policy recommendations. Highlights: The analysis of the planning system in Catalonia is carried out. A quantitative novel approach based on network analysis has been used. There are different management traditions depending on the type of risk. Climate change is weakly present in the statutory planning. The method is useful to illustrate and quantify complexity.